Effectiveness of Tourist Area based Waste Management Legal in The Malioboro Yogyakarta Tourism Center - Aditya Ananda; Nunik Nurhayati; R Rizka; Arief Budiono (Universitas Muhammadiyah Surakarta, 2023)
This article aims to determine the effectiveness of the law regarding tourism-based waste management carried out by the Yogyakarta City Government, targeting the center of the Malioboro Tourism Area as one of the waste producers. This research uses empirical legal methods which are deductive and analyzed qualitatively. Research Location in the Malioboro Tourist Area, Yogyakarta City, Yogyakarta Special Region. This research uses library study data sources, interviews with Yogyakarta City DLH employees and questionnaire techniques for tourists. Then it is processed to get answers to problems related to waste management in the city of Yogyakarta. This research aims to find out 1) There is an overview of waste management in the Jalan Malioboro Tourist Area in terms of Regional Regulation Number 1 of 2022 concerning waste management which describes the technical waste management carried out by the Yogyakarta City Government starting from monitoring the implementation of tourist waste management and the flow of waste sorting. to Final Waste Processing. Then you can describe 2) The effectiveness of waste management in the Malioboro Tourism Area and explain the theory of effectiveness based on the five factors that support implementation in the sectors of legal rules, law enforcement, infrastructure, society and culture. With awareness of protecting the environment carried out by the community and firmness from the Yogyakarta City Government, and carrying out outreach regarding compliance with protecting the environment, especially waste, to tourists and the surrounding community.